Neither backlash nor convergence: Dynamics of intra-couple childcare division during the Covid-19 pandemic in Germany - Christina Boll; Dana Müller; Simone Schüller (Journal for Labour Market Research, 2023)
Using unique (bi)monthly panel data (IAB-HOPP) covering the immediate postlockdown period from June to August 2020, as well as the subsequent period up until the second lockdown in January/February 2021, we investigate opposing claims of widening/closing the gender gap in parental childcare during the Covid-19 pandemic in Germany. We consider prepandemic division as a reference point and provide dynamics rather than snapshots. Our results suggest a slight initial shift toward a more egalitarian division that, however, faded out in subsequent months. Starting from a fairly 'traditional' prepandemic childcare division, the lockdown stimulus was not nearly strong enough to level the playing field. Subgroup analysis differentiating between individual lockdown-specific work arrangements shows that the drivers of the observed shift were mothers with relatively intense labor market participation who cannot work from home. Fathers' work arrangement instead did not play a significant role. We conclude that the shift emerged out of necessity rather than opportunity, which makes it likely to fade once the necessity vanishes. Further, a shift is observed only if fathers were to some extent involved in childcare prepandemic, which points to the crucial role of initial conditions.
Keywords: D13; J13; J16; 330; Covid-19; Intra-couple division of unpaid work; Childcare; Gender; Working from home; IAB-HOPP